Responses of tiba on growth, yield and biochemical components of BARI Maize-6 (Journal of Bangladesh Academy of Sciences, 2024)
A field trial was carried out to investigate the responses of TIBA (0, 25, 50, 75, and 100 ppm) on growth, yield, and biochemical components of BARI Maize-6. Results revealed that plant height gradually reduced with the rising levels of TIBA but non-significantly. The application of 75 ppm TIBA resulted in the highest number of leaves and maximum dry weight of leaves and stems, whereas the dry weight of leaves was significantly higher than that of the control. Plants treated with 50 ppm TIBA resulted in maximum dry weight of roots, absolute growth rate, and relative growth rate, but statistically, they were at par with the rest of the treatments. The total number of cobs per plant was noted to be the highest at 50 ppm, followed by 75 ppm TIBA. Application of 75 ppm TIBA produced the highest fresh (127.10 g) and dry (111.51 g) weight of cobs, the longest cob (17.07 cm), the maximum number of kernels per row (31.81) and cob (408.17), dry weight of tassel (3.75 g), yield per plant (107.07 g) yield per hectare (7138.08 kg) and harvest index (89.72%). Significantly higher values were noted in the case of fresh and dry weight of cobs, number of kernels per cob, yield per plant, and yield per hectare. Yield per plant due to 75 ppm TIBA increased by 65.72% over control. Pigment contents of leaves responded positively following most of the TIBA treatments except chl. a content at the tassel initiation stage. Positive responses of TIBA in the protein content of leaves were also obtained in most cases. The maximum protein content of seeds was recorded from 50 ppm (94.88 mg/g) followed by 75 ppm (83.94 mg/g) TIBA but with a similar statistical identity. Among five treatments, 75 ppm TIBA produced better stimulations.J. Bangladesh Acad. Sci. 48(1); 45-50: June 2024